Development of endometrial stromal sarcoma in a patient undergoing in vitro fertilization: A case report - Tulsi Patel; Jessica N. Sosa-Stanley; Emily Evans-Hoeker; Janet L. Osborne (Elsevier, 2020)
Development of endometrial stromal sarcoma during in vitro fertilization (IVF) is rare. We encountered a case of endometrial stromal sarcoma (ESS) presenting as a new endometrial mass in a patient undergoing donor egg IVF, despite normal imaging and exams prior to and throughout treatment. To our knowledge, this is the only report describing the rapid growth of ESS during IVF treatment. When diagnosing an endometrial stromal sarcoma, it is important for the clinician and patient to be aware that full histologic inspection is required to distinguish it from a benign neoplasm. Given the need for a hysterectomy for definitive diagnosis, this case presents ethical challenges and potential for patient distress.